De um nascimento a outro : o processo de filiação numa adoção de crianças maiores - Speck, Sheila (2013)
The adoption context of older children faces confrontation between past and present. It is made of stories that intersect and merge into the new gathering. Thereby, we highlight the importance of considering such dynamics and the resulting effects from old bonds on the new adoptive filiation construction. From this perspective, we have done a meta-analysis study of the dissertation The Process of Becoming a Father, a Mother, and Children in the Adoption of Older Children. Based on accounts collected along the judicial dismissal period and in the adjustment period follow up, we were able to reconstruct part of the children s and the adoptive families stories and, then, conduct a clinical analysis from a psychoanalytical bias. The present study has demonstrated that the old parental imagos and the marks from the previous story never cease to re-inscribe themselves. It has also been shown that distressing situations from the prospective adopted children s past trigger defenses and interfere in the new affective bonds. This study has pointed out the need to consider the prospective adopted child s previous life and also the importance of the adjustment period, since the new filiation construction has its start during this time.